Aischinou ho kata Ktēsiphōntos logos. Aeschinis in Ctesiphontem oratio. - Aeschines. (Tufts University. Tisch Library., 2015)
1 online resource (vii, [1], 92, iv, 107, [1] pages); The first five words of the title are transliterated from the Greek.; Greek text, followed by the Latin.; With a half-title.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: Gaskell,640; Indexed in: English Short Title Catalog,ESTCT86589